Pengintegrasian Nilai Karakter dan Nilai Konservasi Pembelajaran Matematika Kurikulum Merdeka di Era Teknologi Society 5.0 - Sarah, Caecillia Rafika; Zaenuri, Zaenuri; Mulyono, Mulyono; Walid, Walid; Kharisudin, Iqbal (Suska Journal of mathematics Education, 2023)
Education is a determinant of the quality of human resources in a nation, which can guide the nation's development in a better direction in various aspects. The implementation of the Independent Curriculum in education is in line with new concepts in the social and technological world, namely the Industrial Revolution Society 5.0, which enables humans (to utilize modern-based knowledge, one of which is in the process of implementing character and conservation values in schools. This research aims to examine the integration of character values and conservation values through independent curriculum mathematics learning in the technological era of society 5.0. The research method used is a literature study through the study of scientific articles, books, journal proceedings, and other scientific literature. The data is analyzed descriptively to determine the relationship between one aspect and another. Based on the results of the literature study, it can be concluded that character and conservation values in mathematics learning can be integrated through a fun learning process in accordance with the concept of an independent curriculum in the era of society 5.0 in 21st century learning, namely a new learning paradigm that has learning objectives, a learning process and an assessment process carried out to ensure that students' character and conservation values are achieved and realized through the pancasila student profile.